Confronting Ebola as a Sexually Transmitted Infection - Fischer, William A. (Clin Infect Dis, 2016)
The unprecedented Ebola outbreak that devastated West Africa evolved within months from a regional outbreak to a global public health emergency. While the rate of confirmed cases declined dramatically, sporadic clusters of Ebola virus disease (EVD) continue well beyond the double incubation period of 42 days used to declare a nation Ebola-free. At the same time, evidence that the virus persists in genital fluids and can be sexually transmitted, along with the potential for lingering virus in other body compartments to permit recrudescence of EVD, has shaken our thinking of what it takes to achieve lasting control of an Ebola epidemic. A comprehensive response to the threat of persistence and sexual transmission of Ebola is required and should build on accessible longitudinal medical care of survivors and accurate genital fluid testing for Ebola. Control of this and future Ebola outbreaks will depend on our ability to recognize and respond to this persistence of the virus in those who survive.